Photoswitchable inhibitors of human β-glucocerebrosidase. Issue 8 (2nd February 2022) - Davighi, Maria Giulia; Clemente, Francesca; Matassini, Camilla; Cardona, Francesca; Nielsen, Mogens Brøndsted; Goti, Andrea; Morrone, Amelia; Paoli, Paolo; Cacciarini, Martina
Abstract : Towards human GCase activity enhancement by means of light responsive inhibitors. Abstract : Light-switchable inhibitors of the enzyme β-glucocerebrosidase (GCase) have been developed by anchoring a specific azasugar to a dihydroazulene or an azobenzene responsive moiety. Their inhibitory effect towards human GCase, before and after irradiation are reported, and the effect on thermal denaturation of recombinant GCase and cytotoxicity were studied on selected candidates.